2020
DOI: 10.1200/edbk_279867
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Colorectal Cancer by Tumor Biology

Abstract: Colorectal cancer treatment has undergone a paradigm shift. We no longer see this disease as a singular, anatomic tumor type but rather a set of disease subgroups. Largely because of a better understanding of cancer biology and the introduction and integration of molecular biomarkers—the premise of precision therapy—we are beginning to direct treatments toward the right tumor target(s) in the right patients. The field of molecular profiling is continually evolving, and new biomarkers are constantly being disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 118 publications
(118 reference statements)
0
16
0
1
Order By: Relevance
“…As with other malignancies, such as lung cancer, 16 there is increasing emphasis on identifying key oncogenic drivers that define molecular sub-types of metastatic colorectal cancer (mCRC) and in developing effective targeted therapies tailored to the oncogenic drivers. 6 , 17 Epidermal growth factor receptor (EGFR) plays an important role in the normal function of gastrointestinal tissue and a prominent role in the development of neoplasia in colonic epithelium. EGFR regulates proliferation and migration in the intestinal epithelium, which is a highly dynamic tissue.…”
Section: Current Biomarker-based Stratification Of Mcrcmentioning
confidence: 99%
See 1 more Smart Citation
“…As with other malignancies, such as lung cancer, 16 there is increasing emphasis on identifying key oncogenic drivers that define molecular sub-types of metastatic colorectal cancer (mCRC) and in developing effective targeted therapies tailored to the oncogenic drivers. 6 , 17 Epidermal growth factor receptor (EGFR) plays an important role in the normal function of gastrointestinal tissue and a prominent role in the development of neoplasia in colonic epithelium. EGFR regulates proliferation and migration in the intestinal epithelium, which is a highly dynamic tissue.…”
Section: Current Biomarker-based Stratification Of Mcrcmentioning
confidence: 99%
“…Activating mutations in these downstream signaling pathways negate the efficacy of anti-EGFR therapy necessitating screening to identify patients who are unlikely to respond to expensive therapy. 17 The use of an extended RAS panel that screens not only for the >40% of CRC with activating KRAS mutations in exon 2, but also for mutations in exons 3/4 of KRAS and exons 1/2/3/4 of NRAS (~20% of patients without exon 2 KRAS mutations), 25 more broadly detects RAS-related resistance to anti-EGFR therapies, 26 and is recommended by the National Comprehensive Cancer Network. In principle, the activating mutations in KRAS that preclude use of anti-EGFR therapy in mCRC could be targeted by RAS-specific agents including AMG510, which targets KRAS G12C .…”
Section: Current Biomarker-based Stratification Of Mcrcmentioning
confidence: 99%
“…Nowadays, testing KRAS, NRAS, and MSI has become a fundamental disease-management step to set a therapeutic program requiring personalized therapy, especially for metastatic patients [60]. Studying KRAS and NRAS mutations is the key to select patients that could respond to Cetuximab and Panitumumab anti-EGFR program therapies [61]. Over the last ten years the EFGR pathway has become the first target therapy and 25-40% of CRC patients are quadruple-negative (KRAS/ NRAS/BRAF/PI3KCA wild type) [62].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…This condition is related to a low possibility to have a good response to all target therapies [62]. In refractory cases, a study of Her-2 amplification and NTRK1, ALK, or ROS1 targets could also be considered [61].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…In the studies that have reported ctDNA analysis in metastatic CRC patients, three different approaches have been used: (i) in the studies that involved analysis of a few mutations, such as RAS or BRAF mutations, the assays were based on PCR analysis, for example, the use of BEAMing or droplet digital PCR to detect mutations with extremely low mutant allele fraction; (ii) targeted NGS panel was utilized for the detection of multiple mutations, although with lower sensitivity compared to PCR; (iii) whole-exome or whole-genome sequencing was used, in which the amplitude of genomic coverage is achieved at the expense of depth of coverage [62]. Therefore, the application of ultra-deep targeted sequencing using digital droplet PCR was able to improve the capacity of detecting cfDNA somatic alterations with a variant allele frequency as low as 0.18% [63].…”
Section: Ctdna In Colorectal Cancermentioning
confidence: 99%